Globalization and its impact on business strategies - Solovyev, Stepan; Pichanič, Mikuláš, 1942-; Říha, David; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This master thesis concerns the topic of cultural differences and globalization, that is a very important and popular topic in the modern world nowadays, orientated towards rapidly developing economies. This diploma thesis is based on the study of the culture of China and India.The main aim of the master thesis is to formulate suggestions that could be utilized to promote the products of Kofola company in terms of cultural differences for future operating company in the selected markets. The main aim is divided into two partial goals. The first partial goal is to analyze the markets of the selected countries – India and China. The second partial goal is to formulate recommendations on how to run a business successfully, in these countries.There were identified following suggestions for Indian market: a joint venture is the most logical arrangement for operating the business, concentrate on cities in the south of the country, the advertising should be performed in the English language but local languages should be taken into account too, the focus group could be formed by Early Young Adults, the best way to sell the product is via restaurants and the main idea of the advertising campaign should be – youth and spending time together. It would be ideal to involve local actors in the advertisement.For Chinese market it is necessary to cooperate with a local partner, to promote the fact that the company comes from Europe, to emphasize the product of the company is not as harmful as its competitors, and lastly to cooperate with bloggers.
Vedoucí práce: Mikuláš Pichanič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses